2015
DOI: 10.7566/jpsj.84.034706
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity in FeTe1−xSx Induced by Electrochemical Reaction Using Ionic Liquid Solution

Abstract: Superconductivity in FeTe 0.8 S 0.2 is successfully induced by an electrochemical reaction using an ionic liquid solution. A clear correlation between the Fe concentration in the solution and superconductivity was confirmed, suggesting that superconductivity is induced by the deintercalation of excess Fe.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
4
1
Order By: Relevance
“…Next, we investigated the resistivity of FeSe 0.2 Te 0.8 immersed in the ionic liquid at 80 °C with no voltage application. In contrast to previous reports on FeS 0.2 Te 0.8 , 7,8) we found that T onset c for the sample KE33 (L = 60 µm, W = 100 µm, without FIB etching) is enhanced by roughly ∼0.5 K after long soaking for 360 min, as shown in Fig. 3.…”
contrasting
confidence: 99%
See 3 more Smart Citations
“…Next, we investigated the resistivity of FeSe 0.2 Te 0.8 immersed in the ionic liquid at 80 °C with no voltage application. In contrast to previous reports on FeS 0.2 Te 0.8 , 7,8) we found that T onset c for the sample KE33 (L = 60 µm, W = 100 µm, without FIB etching) is enhanced by roughly ∼0.5 K after long soaking for 360 min, as shown in Fig. 3.…”
contrasting
confidence: 99%
“…The tunability of superconducting properties is crucially important. In this regard, an electrochemical method is very attractive, because it can be used to deintercalate interstitial Fe, 7,8) intercalate the spacer layers, 3) etch a surface chemically, and form a field-effect transistor (FET) utilizing the EDL structure. 4) However, this method has been applied to only polycrystalline powders and thin films, since the moving distance of ions in solids during electrochemical reactions is very short, thus requiring a large surface area per unit volume to obtain a sufficient degree of change.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The acid and alcoholic beverage effects were further improved to become a more controllable electrochemical reaction method performed by a standard three-electrode method [55,56]. A Ag plate and a Pt mesh were used as the reference and counter electrodes, respectively, while an FeTe 1−x S x sample was used as the working electrode.…”
Section: Annealing In Various Atmospheres and Liquidsmentioning
confidence: 99%